Strategi pengaktifan kelompok bina keluarga balita pada kampung keluarga berencana - Eddy Munawar; Gema Novi Renggina (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
Family Planning Village (KB) was one of the flagship programs of the Indonesian National Population and Family Planning Agency (BKKBN). IT aimed to synergize the Concept of Family Empowerment Development, Population and Family Planning (Bangga Kencana) in the village sphere. That could improve the utilization of Family Planning services can be accessed by people living in remote villages from family planning service centres and as an effort by BKKBN to create a prosperous and quality family. One of Bangga Kencana mandatory programs in Kb Village was the Toddler Family Development Program (BKB). This community empowerment activity was carried out to activate the BKB group by conducting counselling, coaching, monitoring, and field assistance. From the assessment results, after the training was carried out. It appeared that the cadres of BKB Group did coach public dissemination better. They were proven from the effects of Pre-Test, and Post-Trial Cadre Supervisor BKB where the initial pre-test score averaged 65.5%, after conducting evaluation and education then done Post Test, where the average weight increased to 84.76%. Then there was the recognition of the community based on the results of in-depth interviews that there is an increase in public awareness to participate in the active group of BKB and increase the participation of citizens in every BKB Group coaching activity in Lhambuk Village.